2014
DOI: 10.3198/jpr2014.04.0022crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Egan’ Wheat with Resistance to Orange Wheat Blossom Midge

Abstract: ‘Egan’ hard red spring wheat (Triticum aestivum L.) (Reg. No. 1102, PI 671855) was developed by the Montana Agricultural Experiment Station and released in 2014. Egan is intended for production in areas of Montana infested with the orange wheat blossom midge (OWBM) (Sitodiplosis mosellana Géhin). Egan is resistant to OWBM due to antibiosis conferred by resistance gene Sm1. Egan also contains a chromosome segment originally introgressed into wheat from T. turgidum ssp. dicoccoides containing a gene for high pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Although late‐season N addition for protein has not been profitable (Chen et al, 2008), it is imperative to find a cultivar that produces high yield without sacrificing quality. Recently (after this research concluded), Montana spring wheat breeder released cultivar ‘Egan’ (Blake et al, 2014), a HRSW with the Gpc‐B1 gene for high protein, resistant to orange wheat blossom midge [ Sitodiplosis mosellana (Géhin)] having high FN. Its performance with respect to different irrigation strategies is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although late‐season N addition for protein has not been profitable (Chen et al, 2008), it is imperative to find a cultivar that produces high yield without sacrificing quality. Recently (after this research concluded), Montana spring wheat breeder released cultivar ‘Egan’ (Blake et al, 2014), a HRSW with the Gpc‐B1 gene for high protein, resistant to orange wheat blossom midge [ Sitodiplosis mosellana (Géhin)] having high FN. Its performance with respect to different irrigation strategies is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat grain quality is mainly determined by endosperm texture (i.e., grain hardness), protein content, and gluten strength [4], which are affected by genetics and environment, as well as their interaction [5][6][7][8][9][10][11]. For instance, grain protein content and gluten strength are related to loci for high molecular weight glutenin subunits (e.g., Glu-A1, Glu-B1, Glu-D1) and the introgression of high grain protein genes (e.g., Gpc-B1) [12][13][14]. Among the many environmental factors affecting wheat quality, the availability of water and nitrogen (N) is often the most influential [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, demand for alternative methods to control S. mosellana populations has been recently stimulated due to the increased risk of insecticide resistance development from the repeated/heavy use of insecticides, and the concerns associated with the environment and human health (Koureas et al ., ; Kim et al ., ). Potential alternative methods for wheat midge control include the use of resistant wheat varieties (Blake et al ., ; Chavalle et al ., ) and natural enemies such as parasitoids, for example, Macroglenes penetrans (Kirby) (Hymenoptera: Pteromalidae), Euxestonotus error (Fitch) and Platygaster tuberosula (Kieffer) (Hymenoptera: Platygastridae) (Olfert et al ., ; Shanower, ; Thompson & Reddy, ), and predators (Floate et al ., ; Holland et al ., ). Wheat midge resistant wheat varieties have been developed in many parts of the world (e.g., Canada, Europe and US) and shown great potential for suppressing S. mosellana population (Lamb et al ., ; Blake et al ., ; Chavalle et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Potential alternative methods for wheat midge control include the use of resistant wheat varieties (Blake et al, 2014;Chavalle et al, 2014) and natural enemies such as parasitoids, for example, Macroglenes penetrans (Kirby) (Hymenoptera: Pteromalidae), Euxestonotus error (Fitch) and Platygaster tuberosula (Kieffer) (Hymenoptera: Platygastridae) (Olfert et al, 2003;Shanower, 2005;Thompson & Reddy, 2016), and predators (Floate et al, 1990;Holland et al, 1996). Wheat midge resistant wheat varieties have been developed in many parts of the world (e.g., Canada, Europe and US) and shown great potential for suppressing S. mosellana population (Lamb et al, 2002;Blake et al, 2014;Chavalle et al, 2017). Wheat variety resistance to S. mosellana is linked to antixenosis (oviposition deterrent activity) or antibiosis (larval death occurrence due to presence of Sm1 gene) mechanisms (Lamb et al, 2002;Blake et al, 2014;Chavalle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation